Short-term biomechanical adaptation in a maximum velocity field sport sprinting protocol: Pilot investigation - Wdowski, M.; Gittoes, M.; Irwin, G.; Nokes, L.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The aim of this study was to investigate short-term biomechanical adaptation of maximum velocity running in response to two sprint protocols; anticipated, where the athlete knew and unanticipated, where he didn't know the required sprint distance prior to entering a test zone. An automatic motion analysis system was used to track sagittal plane marker locations during anticipated and unanticipated maximum velocity sprints performed by an experienced male university football player (age: 23 years, body mass: 85 kg, stature: 1.86 m). Significant increases for the anticipated condition (p <0.05) were found in the step length (0.03 m) and flight distance (0.02 m) over the first 20 m. These short-term technique adaptations indicated that sprint-training protocols for open skill sports may facilitate greater specificity in training by integrating unanticipated movement tasks.